1983
DOI: 10.4269/ajtmh.1983.32.931
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in Hospital Patients with Gastroenteritis

Abstract: Among 884 hospital patients with gastroenteritis, 36 (4.1%) were excreting Cryptosporidium oocysts in their stools; only 5 of the 36 patients were also excreting other enteropathogens, while none of 320 hospital patients without gastroenteritis were excreting Cryptosporidium oocysts. Children were more commonly infected with Cryptosporidium (4.8%) than were adults (1.6%). The prevalence of infection was higher (7%) during the summer period of February-May 1981 than in the remainder of the observation period to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
3
3

Year Published

1985
1985
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 0 publications
1
54
3
3
Order By: Relevance
“…Early reports often described the detection of human cryptosporidiosis in adults, reflecting a high proportion of immunocompromised subjects. However, sporadic infections at the community level were also noted in the early 1980s, particularly in otherwise healthy immunocompetent children (8,9,15,45). Subsequent studies have confirmed a peak incidence in children aged 1 to 5 years in most areas, but the ages are generally at the lower end of that range in developing countries.…”
Section: Discussionmentioning
confidence: 94%
“…Early reports often described the detection of human cryptosporidiosis in adults, reflecting a high proportion of immunocompromised subjects. However, sporadic infections at the community level were also noted in the early 1980s, particularly in otherwise healthy immunocompetent children (8,9,15,45). Subsequent studies have confirmed a peak incidence in children aged 1 to 5 years in most areas, but the ages are generally at the lower end of that range in developing countries.…”
Section: Discussionmentioning
confidence: 94%
“…This occurred in both years, and appears to be extending again into the third year. A survey in Costa Rica detected peaks in two summers (Mata et al 1984) and a 16-month survey in Australia detected a summer peak which did not occur the following year (Tzipori et al 1983); a 12-month survey in the USA noted a late summer, early autumn peak (Wolfson et al 1985). In livestock farming areas the incidence of human infection may be affected by that in newly born animal hosts, and more information is needed to establish other reasons for seasonal variations.…”
Section: Discussionmentioning
confidence: 99%
“…(Robinson et al 1986), 6-1 % in Bangladesh (Shahid et al 1985), 7-9 % reported from Liberia (Hojlyng et al 1984) and 3-0 % and 10X4 % among children and adults respectively in Rwanda (Bogaerts et al 1984). In Liverpool, UK, Canada and Australia, detection rates of 1-4 %, 1-2 % and 4-1 % respectively have been reported Ratnam et al 1985;Tzipori et al 1983). …”
Section: Methodsmentioning
confidence: 99%